PENGARUH UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING - Imam Wahyudi; Nugroho Mardi Wibowo; C. Sri Hartati (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
The purpose of this study is to describe and analyze the effect of company size on earnings management through the profitability of the Automotive & Component Industry Companies listed on the IDX. This type of research is a quantitative descriptive research. The population in this study are Manufacturing Companies in the Automotive & Components Miscellaneous Industry sub-sector which are listed on the IDX for the 2018-2021 period. A sample of 8 companies was obtained from purposive sampling technique. Data analysis technique uses Partial Least Square (PLS). Based on the results of the analysis, it was found that company size has no significant effect on company profitability, company size has a significant positive effect on company earnings management, profitability has a significant effect on company earnings management, company size has no significant effect on earnings management with profitability as an intervening variable in automotive & automotive industry companies. Components listed on the IDX.